2005
DOI: 10.1258/1357633054893364
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology as a filtering system in pigmented lesion clinics

Abstract: Teledermatology was evaluated as a filtering system for a pigmented lesion clinic (PLC). A total of 219 teleconsultations were received at the PLC in a 12-week period. The outcome of the teleconsultation was that 49% of patients were referred to the face-to-face clinic. Teleconsultation reports were available to the general practitioner (GP) in a mean time of 44 h and patients attended the face-to-face clinic within the following two weeks. Agreement between different dermatologists was almost perfect, with k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 0 publications
0
66
0
1
Order By: Relevance
“…10 The other studies had more than one teledermatologist. [14][15][16][17][18][19][20][21] Of the four studies, measuring inter-observational agreement for in-person exams, two showed significantly better agreement among in-person clinicians than distant teledermatologists, 11,12 especially for primary diagnoses, and two did not. 10,13 A PubMed search for teledermatology research done after the latest research reviews published in 2011 9 identified only one additional study having two in-person dermatologists.…”
Section: Introductionmentioning
confidence: 94%
“…10 The other studies had more than one teledermatologist. [14][15][16][17][18][19][20][21] Of the four studies, measuring inter-observational agreement for in-person exams, two showed significantly better agreement among in-person clinicians than distant teledermatologists, 11,12 especially for primary diagnoses, and two did not. 10,13 A PubMed search for teledermatology research done after the latest research reviews published in 2011 9 identified only one additional study having two in-person dermatologists.…”
Section: Introductionmentioning
confidence: 94%
“…All studies used a repeated measures study design with the exception of one randomized controlled trial. 11 Based on location, most of the studies were conducted in the United States (n = 14), [3][4][5][6]22,24,25,33,35,37,[41][42][43]45 followed by the United Kingdom (n = 9), 11,12,15,18,29,30,32,38,44 Italy (n = 6), 7,8,20,21,36,39 Spain (n = 4), 9,10,13,17 Australia/New Zealand (n = 3), 14,31,40 Turkey (n = 2), 16,19 and one study each from Germany, 23 Netherlands, 24 Pakistan, 27 Brazil, 28 and Switzerland. 34 Patient and skin condition characteristics.…”
Section: Summary Of Studies For Key Questions 1 Andmentioning
confidence: 99%
“…Fourteen studies included subjects younger than 18 years. 3,6,8,13,14,16,17,20,21,29,30,35,36,39 In 22 studies reporting gender, most of the subjects were male (57% overall, range 29%-98%). Only 6 studies, all conducted in the United States, reported racial or ethnic characteristics.…”
Section: Summary Of Studies For Key Questions 1 Andmentioning
confidence: 99%
“…Therefore, teledermatology did not develop until the 1990s 4) , but has been utilised in many fields of application since then. It can be applied to melanoma screenings [7][8][9][10] , in the surveillance of the long-term therapy of leg ulcers 11) , or in medical attendance in rural or remote areas 12,13) . There is ample proof that telecare and teledermatology is practicable and well accepted by patients [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%